Bioprinting using PEGDMA-based hydrogel on DLP printer. (2022) - Chang, Shu-Yung; Ching, Terry; Hashimoto, Michinao
Abstract: The ability to create biological tissues with high level of biomimicry is highly sought for in applications for therapeutic screening, disease modelling and regenerative medicines. This paper describes the formulation of poly(ethylene–glycol)-dimethacrylate (PEGDMA)-based bioinks for application in digital light processing (DLP) printers. Poly(ethylene–glycol) (PEG)-based polymers, such as high molecular weight poly(ethylene–glycol)-diacrylate (PEGDA) have been employed in photopolymerization in three-dimensional (3D) cell culture. However, without chemical modification, PEGDA does not promote high cell viability and proliferation. PEGDMA has been reported to support cell attachment without modification, but its application in 3D bioprinting has not been fully explored. To bridge this gap, this study investigated the suitability of PEGDMA as a component of a bioink. We found that PEGDMA could be polymerized alongside with gelatin methacrylate (GelMA) to enable high precision bioprinting while supporting high levels of cell viability and growth. This work demonstrates the potential of PEGDMA as a photo-crosslinkable bioink that can potentially be applied in rapid additive manufacturing of complex 3D bioprinted products.